Analisis Tingkat Kepuasan Konsumen Terhadap Sayuran Produk Elcomar Hydroponics (Studi Kasus : Yogya Supermarket, Kecamatan Sumber, Kabupaten Cirebon) - Fathan, Niko Syauqi; Lumongga, dumasari; Utami, Pujiati (Jurnal Agribisnis dan Pembangunan Pertanian (JAPP), 2026)
ABSTRACT This study aims to analyze the level of consumer satisfaction with Elcomar Hydroponic vegetable products at Yogya Supermarket, Sumber Sub-District, Cirebon Regency. Method:The research employs a descriptive method utilizing both qualitative and quantitative approaches. The sample consists of 50 respondents of various ages and backgrounds, selected through anaccidental samplingtechnique. Data analysis was performed using descriptive statistics,Importance-Performance Analysis (IPA), and theCustomer Satisfaction Index (CSI). Consumers perceive the quality of hydroponic vegetables as good, as evidenced by a total score of 1,655 and an average of 236. All indicatorsincluding freshness, appearance, safety, quality consistency, and certificationreceived positive responses, indicating that the products meet consumer standards and expectations. TheImportance Performance Analysis (IPA) results show that most attributes have a conformity level above 97%, reflecting excellent product performance. The primary strengths of the product lie in its price suitability, freshness level, accessibility, and assurance of safety and certification. Furthermore, the consumer satisfaction level falls into the "Very Satisfied" category, with a Customer Satisfaction Index (CSI) of 92.30%. These results demonstrate that the quality, availability, freshness, packaging, and safety of Elcomar Hydroponic products consistently meet or exceed consumer expectations. Conclusion: Overall, consumers exhibit a very high level of satisfaction with Elcomar Hydroponic products. These findings confirm that the product has a positive reputation, superior quality, and significant potential to maintain consumer loyalty.